HUBUNGAN KEDISIPLINAN BELAJAR DENGAN HASIL BELAJAR MATA PELAJARAN FIKIH DI TINGKAT MADRASAH IBTIDAIYAH/SEKOLAH DASAR - Syamsul Ma’arif (STKIP Subang, 2026)
This study aims to examine the relationship between learning discipline and learning outcomes in Fiqh subjects among students at the Madrasah Ibtidaiyah or elementary school level. Learning discipline is one of the internal factors that plays an important role in supporting the success of the learning process, particularly in Fiqh subjects which require not only mastery of concepts but also understanding and application of Islamic values in daily life. Low levels of learning discipline, such as irregular study habits, lack of compliance with learning rules, and low commitment in completing academic tasks, are assumed to influence students’ learning outcomes in Fiqh. This research employed a quantitative approach using a correlational research design. The research subjects were fifth and sixth grade students of Madrasah Ibtidaiyah in the current academic year, selected through a random sampling technique. Data on learning discipline were collected using a questionnaire developed based on indicators of learning discipline, while data on learning outcomes in Fiqh were obtained from documented evaluation scores. Data analysis was conducted using descriptive statistics and the Pearson Product Moment correlation test to determine the relationship between learning discipline and learning outcomes in Fiqh. The results of the study indicate that students’ learning discipline levels are generally categorized as high, while learning outcomes in Fiqh fall into the moderate to high category. The correlation analysis reveals a positive and significant relationship between learning discipline and learning outcomes in Fiqh subjects. These findings suggest that higher levels of learning discipline are associated with better learning outcomes in Fiqh. Therefore, learning discipline plays a strategic role in improving students’ learning outcomes in Fiqh at the Madrasah Ibtidaiyah or elementary school level. This study is expected to serve as a reference for teachers and schools in developing learning strategies that emphasize the strengthening of students’ learning discipline.